Income and working time of a Fencing Master in Bologna in the 15th and early 16th century - Alessandro Battistini; Niki Corradetti (Acta Periodica Duellatorum, 2016)
Since ancient times, the master-at-arms profession has always been considered essential for the education of the nobility and the common citizenship, especially in the Middle Ages. Yet, we know nothing about the real standard of living of these characters. The recent discovery of documents, which report the sums earned by fencing masters to teach combat disciplines, has brought us the possibility to estimate how highly this profession was regarded, and what its actual economic value was in the Italian late Middle Ages. They also give us also a material view into the modes of operation of a sala d’arme in those times.